2020
DOI: 10.7717/peerj.8985
|View full text |Cite
|
Sign up to set email alerts
|

Invasive crayfish does not influence spawning microhabitat selection of brown frogs

Abstract: Microhabitat selection is a key component of amphibian breeding biology and can be modulated in response to the features of breeding sites and the presence of predators. Despite invasive alien species being among the major threats to amphibians, there is limited information on the role of invasive species in shaping amphibians' breeding microhabitat choice. The invasive red swamp crayfish (Procambarus clarkii) is a major predator of amphibians' larvae, including those of the brown frogs Rana dalmatina and Rana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Both species survived the Pleistocene glaciations in single refugia in southern Europe (Ficetola et al 2007;Vences et al 2013), but while R. dalmatina has expanded its range to much of the territories of central Europe, R. latastei has remained endemic to northern Italy and to neighboring territories (Sillero et al 2014). In sympatry, the two species often share the same breeding site, although R. latastei lays eggs in deeper water, farer from the shoreline (Romagnoli et al 2020). In previous studies (Castellano et al 2022;Castellano et al 2023), we showed that tadpoles of the two species differed in their behavior, both quantitatively (the amount of swimming) and qualitatively (speed and duration of swimming), with R. dalmatina moving more and faster than R. latastei.…”
Section: Introductionmentioning
confidence: 61%
“…Both species survived the Pleistocene glaciations in single refugia in southern Europe (Ficetola et al 2007;Vences et al 2013), but while R. dalmatina has expanded its range to much of the territories of central Europe, R. latastei has remained endemic to northern Italy and to neighboring territories (Sillero et al 2014). In sympatry, the two species often share the same breeding site, although R. latastei lays eggs in deeper water, farer from the shoreline (Romagnoli et al 2020). In previous studies (Castellano et al 2022;Castellano et al 2023), we showed that tadpoles of the two species differed in their behavior, both quantitatively (the amount of swimming) and qualitatively (speed and duration of swimming), with R. dalmatina moving more and faster than R. latastei.…”
Section: Introductionmentioning
confidence: 61%
“…Such an effect could occur because adult females might be able to detect the presence of crayfish and prefer to breed in uninvaded wetlands, or because the crayfish reduces recruitment of juveniles, hampering population growth over time. Brown frog tadpoles can modify development rates in the presence of the alien crayfish (Melotto et al, 2020; Muraro et al, 2021), but no information is available about the ability of adults to detect the predator (Ficetola et al, 2011; Romagnoli et al, 2020). Evidence from related frog species suggested that adults are not able to recognize predators inside breeding wetlands (Laurila & Aho, 1997), still some amphibian species can detect predators and prefer predator‐free ponds for laying eggs (Resetarits, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The two species have different dispersal abilities and lifespan: ~1500 m dispersal and 5–7 years lifespan for R. dalmatina while for R. latastei dispersal ability is ~1000 m and lifespan is 3–4 years (Bernini, Guarino, et al, 2007; Guarino et al, 2003). They very often breed in the same sites, but they exploit different sectors of ponds, with R. dalmatina mostly laying clutches close to the shoreline, while within the same pond, R. latastei prefers sectors far from the shoreland and with deep water (Romagnoli et al, 2020). The two species also have different conservation statuses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations